Relationship between Oral Hygiene and Dietary Behaviour and Dental Caries Status in Primary School Children (KEMAS: Jurnal Kesehatan Masyarakat, 2018)
Tooth decay can be caused by bacteria that live in the mouth. These bacteria feed on food leftovers in the teeth and produce acid. This acid destroys the enamel layer, dentine layer, and pulp. The purpose of this study is to analyze the risk factors of dental caries in primary school children. The subjects of this study were 77 students of SD Sendangmulyo 1 Semarang. We used questionnaires, diagnoses, and interviews for data collection. For data analysis, we used descriptive analysis method. The results showed that the most common dental caries risk factor in primary school children was sugar consumption. Up to 72% of children agreed to bring packed meal, 90.7% were used to have a breakfast, 80% used to clean their mouth every day, 70.7% clean their mouth after meals, 64% brush their teeth after eating candy, and 89.3 % brush their teeth before going to bed. There is a relationship between oral hygiene and dietary behavior and dental caries status of primary school children. In conclusion, there is a relationship between oral hygiene and dietary behavior and dental caries status of primary school children.